A method for preparing ferroalloy and geopolymer materials using waste incineration fly ash and iron tailings
Through co-reduction and roasting technology, waste incineration fly ash and iron tailings are converted into ferroalloy and geopolymer materials, solving the problem of resource waste and achieving efficient resource recycling and utilization.
Patent Information
- Application Number
- CN202410687196.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing technology is difficult to effectively utilize waste to incinerate fly ash and iron tailings, resulting in waste of resources and environmental pollution.
Through co-reduction and roasting technology, the waste incinerated fly ash and finely ground iron tailings are mixed, and high-temperature treatment is carried out to prepare ferroalloy and geopolymer materials, and secondary fly ash is obtained through flue gas capture.
Resource utilization of waste incineration fly ash and iron tailings was realized, high-grade ferroalloys and geopolymer materials with high compressive strength were prepared, and the resource recovery rate and utilization efficiency were improved.
Smart Images

Figure CN118497486B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to resource recycling of solid waste, and in particular to a method for preparing ferroalloy and geopolymer materials by utilizing fly ash from garbage incineration and iron tailings. Background Art
[0002] Iron tailings are the waste after iron ore beneficiation and iron concentrate enrichment, and are the main component of industrial solid waste. According to incomplete statistics, more than 10 billion tons of tailings and waste rocks are discharged worldwide each year. There are more than 8,000 state-owned mines and more than 110,000 township collective mines in my country, with nearly 5 billion tons of stockpiled tailings and an annual tailings discharge of more than 500 million tons, of which ferrous metallurgical mines discharge 150 million tons of tailings annually. Since most of the valuable iron has been extracted, the utilization rate of the remaining materials is relatively low, and most of them are stored in tailings ponds. The stored tailings ponds not only occupy a large amount of land, but also are dangerous sources, which pose safety risks. Once an accident occurs, it affects the life safety of surrounding residents. Therefore, it is imperative to develop a method for the comprehensive utilization of iron tailings to achieve the inherent safety of tailings ponds.
[0003] Fly ash from the incineration of domestic waste is a by-product of the incineration process of domestic waste. In recent years, the incineration of domestic waste in my country has developed rapidly, and the amount of fly ash generated by incineration will inevitably increase with the increase in the scale and capacity of domestic waste incineration treatment. In 2022, the amount of fly ash generated by incineration of waste has reached 10 million tons. With the continuous improvement of the flue gas purification level, the fine particles intercepted and captured by the flue gas purification system - fly ash from the incineration of domestic waste (hereinafter referred to as fly ash) have become more and more "dirty". Because it is enriched with highly toxic heavy metals and dioxin pollutants, it is listed as a hazardous waste. The treatment of fly ash has always been the focus and key link in the pollution control and risk management of incineration plants. At present, fly ash from waste incineration is mainly landfilled through solidification and stabilization. Landfilling not only occupies a large amount of land, but also the long-term effectiveness of heavy metals and dioxins in fly ash after solidification and stabilization needs to be continuously verified. The most important thing is that many useful substances in fly ash have not been effectively utilized. Therefore, it is urgent to develop a clean resource utilization method for fly ash from waste incineration. Summary of the invention
[0004] In view of the above problems, the present invention proposes a method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings, which prepares ferroalloy and geopolymer materials while realizing resource utilization of waste incineration fly ash and iron tailings.
[0005] The present invention provides a method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings, which adopts the following technical scheme:
[0006] A method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings, comprising the following steps: uniformly mixing the waste incineration fly ash and finely ground iron tailings, and then performing co-reduction roasting to obtain a roasting product; collecting flue gas during the roasting process to obtain secondary fly ash; and then cooling the roasting product, grinding and magnetic separation to obtain the ferroalloy and geopolymer materials.
[0007] Preferably, the fine grinding method of the iron tailings is as follows: the iron tailings are finely ground using a ball mill or a rod mill, the grinding concentration is 55-70%, the grinding time is 5-25 minutes, and the fineness of the iron tailings after fine grinding reaches -150μm≥80%.
[0008] Preferably, the co-reduction roasting method is as follows: after mixing the waste incineration fly ash and the finely ground iron tailings, the mixture is co-reduction roasted at 1050-1300°C for 30-150 minutes to obtain a roasted product, which is mainly composed of ferroalloy and geopolymer material, and the glass content in the geopolymer material is ≥90%.
[0009] Further preferably, the roasted product is naturally cooled or water quenched and then finely ground and magnetically separated. The fineness of the roasted product after fine grinding reaches 30 to 70% by mass of -0.15 mm, the magnetic field strength of the magnetic separation is 0.6 to 1.5 KGs, the magnetic product is a ferroalloy, and the non-magnetic product is a geopolymer material.
[0010] Preferably, the mass percentage of the waste incineration fly ash is 20-80%, and the mass percentage of the finely ground iron tailings is 20-80%.
[0011] Further preferably, the mass percentages of the main elements of the waste incineration fly ash are as follows: Ca 10-60%, C 5-20%, Si 0.1-10%, Al 0.1-8%, Cl 10-30%, Fe 0.1-8%, Na 0.1-6%, K 0.1-6%, S0.1-3%, and the waste incineration fly ash also includes the following mass percentages of heavy metal elements: Zn 0-1%, Pb 0-1%, Cr 0-1%, Cu 0-1%, Ni 0-1%, and Cd 0-1%.
[0012] Further preferably, the mass percentages of the main components of the iron tailings are as follows: Fe2O3 5-25%, SiO2 25-70%, Al2O3 5-25%, CaO 2-20%, and MgO 2-10%.
[0013] Preferably, during the co-reduction roasting process, a flue gas capture device is used to capture flue gas to produce secondary fly ash, which is a mixture of 10-80% NaCl, 10-80% KCl, 1-10% PbCl2, 1-10% ZnCl2 and 0-10% CdCl2.
[0014] Preferably, the geopolymer material is subjected to secondary fine grinding to a mass fraction of -45µm ≥ 70% and a specific surface area ≥ 400m 2 / kg, to obtain geopolymer material powder, which is an amorphous inorganic material composed of silicon oxide tetrahedron and aluminum oxide tetrahedron.
[0015] More preferably, after the geopolymer material powder, alkali activator and water are evenly mixed, a mixture is obtained, and the compressive strength of the mixture after 28 days is ≥80Mpa, and the flexural strength is ≥8Mpa. The alkali activator is mainly one or more of cement, Ca(OH)2, NaOH, lime and water glass. The amount of the geopolymer material is 80~96%, and the amount of the alkali activator is 4~20%; the water-cement ratio is 0.4~0.7, wherein the mass of the ash is the sum of the geopolymer material and the alkali activator.
[0016] Beneficial effects:
[0017] The present invention uses waste incineration fly ash and iron tailings as raw materials, and obtains three products of ferroalloy, geopolymer material and secondary fly ash through co-reduction reaction. Waste incineration fly ash is a system with high calcium, high chlorine and high carbon, and also contains trace amounts of heavy metals in the form of oxides. Unlike other fly ashes such as blast furnace ash and pulverized coal, waste incineration fly ash is produced by waste incineration, and its composition has a certain relationship with domestic waste. At the same time, since the flue gas from incineration is acidic, a large amount of lime or lime water will be sprayed in during the flue gas purification process for neutralization, so the calcium content in the fly ash is very high. At the same time, due to the dietary habits of the Chinese, the content of Na, K and Cl in the fly ash is also relatively high, so the waste incineration fly ash is mainly composed of calcium-containing substances or chlorides such as NaCl, KCl, CaClOH, Ca(OH)2, CaSO4, etc., and its physical and chemical properties are significantly different from those of other fly ashes such as blast furnace ash and pulverized coal. Iron tailings are a system with high iron, high silicon and a certain amount of aluminum, and the iron in the iron tailings mainly exists in the form of magnetite and pyroxene. The two are processed together at high temperature, and the carbon in the fly ash participates in the reduction reaction as a reducing agent; at the same time, in a high-temperature environment, C reacts with CO2 to generate the reducing agent CO. In a high-temperature reducing atmosphere, magnetite is reduced to metallic iron, and other heavy metals such as copper, nickel and chromium, which mainly exist in the form of oxides and sulfides, are reduced to metals such as copper, nickel and chromium. Copper, nickel and chromium metals are iron-loving and form alloys with metallic iron. Compared with the reduction process that directly uses coal, coke, etc. as a reducing agent, this process not only saves carbon resources, but also avoids the use of additives, and also achieves energy conservation and emission reduction and resource conservation, reducing the process production cost.
[0018] (2) The slag phase in the system is mainly silicon oxide, calcium oxide and aluminum oxide. The SiO2 content in the iron tailings is very high, and the Na and K contents in the fly ash are relatively high. The high content of SiO2 can regulate the melting point of the SiO2-Al2O3-CaO slag phase system. At the same time, with the action of alkaline metals Na and K, these substances are conducive to reducing the melting point of the system to 1050-1300°C, and the system is completely liquid. The high Si content can reduce the viscosity of the system. In a low-viscosity liquid system, iron can quickly aggregate and grow to form large-sized iron particles. The large-sized iron particles gather at the bottom of the system and form alloys with ferrophilic metals. The iron alloy particles of the present invention are relatively pure. Compared with processes such as direct reduction, the iron alloy particle size is above 2 mm and can be seen with the naked eye. The iron alloy particles obtained by the present invention are larger, the magnetic field intensity of magnetic separation is lower, and recovery is easier, so the iron recovery rate is higher than other processes. The monomer dissociation can be easily achieved in the crushing process, and the monomer dissociation can be achieved after fine grinding. The process flow is simpler than the direct reduction process, which reduces the production cost; the grade of the ferroalloy particles can reach more than 93%, the iron recovery rate can reach more than 90%, and it contains metals such as Cu, Ni, Cr, etc., with higher added value, and the recovery of iron-loving heavy metals in fly ash and iron in iron tailings is achieved. The temperature of the coordinated smelting reduction of waste incineration fly ash and iron tailings in the present invention is lower than that of the direct reduction process, and lower than that of the fly ash direct melting process, and the energy consumption is lower.
[0019] (3) The present invention uses a flue gas capture system to capture secondary fly ash. Other heavy metals such as Zn, Pb and Cd are volatile heavy metals, which are easy to react with chlorine in fly ash at high temperature and volatilize into secondary fly ash, obtaining secondary fly ash mainly composed of chlorides such as NaCl, KCl, PbCl2, ZnCl2 and CdCl2, among which the grade of Pb and Zn reaches more than 4%, which can be used as raw materials for industrial Pb and Zn. Therefore, most of the heavy metals in fly ash are effectively recovered, and dioxins in fly ash are effectively decomposed at high temperature, realizing fly ash detoxification and fly ash resource utilization.
[0020] (4) The CaO-SiO2-Al2O3-FeO system reaches a molten state, and after cooling, an amorphous glassy material composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons is obtained. This material has the properties of volcanic ash and can be used as a geopolymer material. The remaining small amount of heavy metals will also be firmly fixed in this amorphous, glassy geopolymer material and it is difficult to release. Under the condition of alkali activator excitation, the activity of the geopolymer material is activated, and the compressive strength after 28 days is ≥80Mpa, and the flexural strength is ≥8Mpa. It has high strength and can replace cement and other cementitious materials. The gelation process of this process is a reaction process in which the silicon-oxygen bonds and aluminum-oxygen bonds in the geopolymer material are broken and then reorganized under the catalysis of the alkali activator to reconstruct a new silicon (aluminum or phosphorus) oxygen tetrahedron structure. It is a geopolymer polymerization process. The final hardened product is still mainly composed of amorphous substances containing silicon (aluminum or phosphorus) oxygen tetrahedron unit structures. The present invention utilizes waste incineration fly ash and iron tailings to prepare ferroalloys, geopolymer materials and secondary fly ash, realizes directional recovery of valuable metals, and simultaneously obtains geopolymer materials with wide application value, thereby improving the consumption capacity of fly ash and iron tailings, reducing the processing cost of fly ash, reducing energy consumption, realizing the resource utilization of fly ash and iron tailings, and providing a new resource utilization path for the disposal of fly ash and iron tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of Embodiment 1 of the present invention;
[0022] Figure 2 The ferroalloy particles are obtained in Example 1 of the present invention;
[0023] Figure 3 The geopolymer material prepared in Example 1 of the present invention;
[0024] Figure 4 XRD of the geopolymer material prepared in Example 1 of the present invention (mainly amorphous structure);
[0025] Figure 5 This is the secondary fly ash prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0027] Example 1
[0028] A method for preparing ferroalloy and geopolymer materials using waste incineration fly ash and iron tailings comprises the following steps:
[0029] The iron tailings were ball milled for 10 minutes at a grinding concentration of 60%, and finely ground to -150μm, accounting for 91%. The waste incineration fly ash with a mass fraction of 30% and the iron tailings with a mass fraction of 70% were mixed evenly and put into a crucible. The crucible was placed in a muffle furnace, roasted at 1050℃ for 150 minutes for co-reduction reaction, and the crucible was taken out of the muffle furnace and cooled by water quenching. Then, the crucible was placed in an oven and dried at 70℃ for 20 minutes. The roasted product was taken out of the crucible and finely ground using a rod mill. The grinding concentration of the fine grinding was 55%, and the grinding time was 5 minutes. After screening, it was found that the mass fraction of the fineness of -0.15mm after the fine grinding was 50%. Finally, the roasted product after the fine grinding was magnetically separated using a magnetic separator with a magnetic field strength of 0.8KGs. The magnetic product is ferroalloy. Ferroalloys such as Figure 2 As shown, the non-magnetic product is a block geopolymer material, the glass content of the geopolymer material is 96%, and the graph and XRD of the geopolymer material are as follows Figure 3 and Figure 4 As shown. According to the test results, the iron grade in the ferroalloy is 93.58%, the iron recovery rate is 90.71%, and it contains trace amounts of Ni, Cu, Cr and other iron-loving metals. During the roasting and reduction process, the secondary fly ash is collected by the flue gas capture system to obtain NaCl 45.13%, KCl 40.98%, PbCl2
[0030] Yellow secondary fly ash composed of a mixture of 4.98%, ZnCl24.73%, and CdCl21.21%. Figure 5 The block geopolymer material was finely ground to -45µm with a mass fraction of 71.58% and a specific surface area of 471m 2 / kg of geopolymer powder, the main phase of which is an amorphous material composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. 96% mass fraction of geopolymer powder is mixed with 4% NaOH, with a water-cement ratio of 0.4. The compressive strength after 28 days is 81Mpa and the flexural strength is 8.2Mpa. The preparation process is as follows Figure 1 In this embodiment, the mass percentages of the main elements of the waste incineration fly ash are as follows: Ca 50.25%, C 10.89%, Si 1.83%, Al 2.11%, Cl 14.14%, Fe 1.14%, Na 2.21%, K4.09%, S 1.56%, and the waste incineration fly ash also includes the following mass percentages of heavy metal elements: Zn 0.48%, Pb 0.12%, Cu 0.08%, Ni 0.02%, Cr 0.12%, and Cd 0.01%.
[0031] The percentages of the main chemical components of the iron tailings are as follows: Fe2O3 12.15%, SiO2 48.50%, Al2O3 16.43%, CaO 8.92% and MgO 5.44%.
[0032] Example 2
[0033] A method for preparing ferroalloy and geopolymer materials using waste incineration fly ash and iron tailings comprises the following steps:
[0034] The iron tailings were ball milled for 5 minutes at a grinding concentration of 55%, and finely ground to -150μm, accounting for 83%. 50% of the waste incineration fly ash and 50% of the iron tailings were mixed evenly and put into the smelting furnace, and melted and reduced at 1300℃ for 30 minutes; the crucible was taken out of the muffle furnace, quenched with water, and then placed in an oven and dried at 70℃ for 20 minutes. Then, the roasted product was finely ground once using a rod mill. The grinding concentration of the fine grinding was 65%, and the grinding time of the fine grinding was 3 minutes. After screening, it was found that the mass fraction of the fine grinding degree of -0.15mm was 30%. Finally, the roasted product after the fine grinding was magnetically separated using a magnetic separator with a magnetic field strength of 1KGs. The magnetic product was ferroalloy, and the non-magnetic product was geopolymer material. The glass content in the geopolymer material was 93%. According to the test results, the iron grade in the ferroalloy is 94.12%, the iron recovery rate is 92.03%, and it contains trace amounts of Ni, Cu, Cr and other iron-loving metals. During the smelting reduction process, the secondary fly ash is captured by the flue gas capture system to obtain a yellow powdery secondary fly ash composed of a mixture of NaCl 43.31%, KCl 40.18%, PbCl25.15%, ZnCl24.02%, and CdCl21.13%. The block geopolymer material is finely ground to a mass fraction of 83.64% and a specific surface area of 537m -45µm. 2 / kg of geopolymer powder, the main phase of which is an amorphous material composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. A mixture of 90% by mass of geopolymer powder, 5% of NaOH and 5% of water glass, with a water-cement ratio of 0.7, has a 28-day compressive strength of 86 MPa and a flexural strength of 8.4 MPa. In this embodiment, the mass percentage of the main elements of the waste incineration fly ash is: Ca 43.52%, C 17.92%, Si 3.77%, Al 2.24%, Cl 16.78%, Fe 1.23%, Na 2.21%, K2.58%, S 0.96%, and the waste incineration fly ash also includes the following mass percentages of heavy metal elements: Zn 0.35%, Pb 0.28%, Cu 0.07%, Ni 0.02%, Cr 0.08%, Cd 0.05%.
[0035] The percentage mass content of the main chemical components of iron tailings are: Fe2O3 22.31%, SiO2 27.45%, Al2O3 23.43%, CaO 16.23% and MgO 1.78%.
[0036] Example 3
[0037] A method for preparing ferroalloy and geopolymer materials using waste incineration fly ash and iron tailings comprises the following steps:
[0038] The iron tailings were ball milled for 25 minutes at a grinding concentration of 70%, and finely ground to -150μm, accounting for 96%. 70% of the waste incineration fly ash and 30% of the iron tailings were mixed evenly and put into a crucible, and then the crucible was placed in a muffle furnace and roasted at 1200℃ for a total of 60 minutes; the crucible was taken out of the muffle furnace, quenched in water, and then placed in an oven and dried at 70℃ for 20 minutes. After drying, the roasted product was taken out of the crucible and finely ground using a rod mill. The grinding concentration was 60% and the grinding time was 8 minutes. After screening, it was found that the mass fraction of the grinding fineness of -0.15mm was 70%. Then, the roasted product after the first fine grinding is magnetically separated by a magnetic separator with a magnetic field strength of 1.5KGs. The magnetic product is ferroalloy, and the non-magnetic product is geopolymer material. The glass content in the geopolymer material is 98%; after chemical analysis, the iron grade in the ferroalloy is 93.21%, the iron recovery rate is 91.59%, and it contains trace amounts of Ni, Cu, Cr and other iron-loving metals. During the roasting reduction process, the secondary fly ash is collected by the flue gas capture system to obtain a secondary fly ash composed of a mixture of NaCl 53.18%, KCl 34.23%, PbCl24.21%, ZnCl24.07%, and CdCl21.13%. The blocky geopolymer material is finely ground for the second time to -45µm with a mass fraction of 91.37% and a specific surface area of 561m 2 / kg of geopolymer powder, the main phase of which is an amorphous material composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. 80% mass fraction of geopolymer powder is mixed with 20% cement, the water-cement ratio is 0.5, the compressive strength after 28 days is 88Mpa, and the flexural strength is 8.9Mpa. In this embodiment, the mass percentage of the main elements of the waste incineration fly ash is: Ca 19.85%, C6.89%, Si 9.58%, Al 7.56%, Cl 28.59%, Fe 8.58%, Na 4.08%, K 1.59%, S 1.20%, and the waste incineration fly ash also includes the following mass percentage of heavy metal elements: Zn 0.35%, Pb 0.28%, Cu 0.07%, Ni 0.02%, Cr0.08%, Cd 0.05%.
[0039] The percentage mass content of the main chemical components of iron tailings are: Fe2O3 8.72%, SiO2 64.56%, Al2O3 11.89%, CaO 2.92% and MgO 2.44%.
[0040] The present invention uses waste incineration fly ash and iron tailings as raw materials, and performs high-temperature synergistic treatment. The carbon in the fly ash and the CO generated by the reaction between the fly ash and CO2 are used as reducing agents. The iron oxide in the magnetite is reduced to metallic iron, and the copper, nickel and chromium in the form of oxides and sulfides are reduced to metals such as copper, nickel and chromium. The high content of SiO2 in the iron tailings can regulate the melting point of the SiO2-Al2O3-CaO slag phase system, and at the same time cooperate with the effects of Na and K in the fly ash to make the melting point of the system 1050-1300°C, which is in a liquid state. The high content of Si can reduce the viscosity of the system. In the low-viscosity liquid system, iron can quickly aggregate to form large-sized iron particles, and form iron alloys with iron-loving heavy metals Cu, Ni and Cr, most of which have a particle size of more than 2 mm. The iron alloy particles of the present invention have a grade of more than 93%, an iron recovery rate of more than 90%, and contain metals such as Cu, Ni, Cr, etc., with higher added value, realizing the recovery of iron-loving heavy metals in fly ash and iron in iron tailings.
[0041] The present invention generates a lot of large ferroalloy particles, so only simple crushing is needed for one grinding to achieve monomer dissociation of large alloy iron particles, thus avoiding the consumption of grinding energy. Compared with other grinding processes, since the prepared iron particles are relatively small, to achieve monomer dissociation, the general grinding fineness is based on -200 mesh reaching more than 80% for grinding, resulting in greater energy consumption. In addition, the magnetic field intensity required by the present invention is also significantly lower than other similar high-temperature reduction processes such as the iron tailings direct reduction process. Since the ferroalloy particles are relatively large, the magnetic field intensity of magnetic separation is relatively low, and recovery is easier, so the iron recovery rate is higher than other processes.
[0042] The present invention utilizes a flue gas capture system to capture secondary fly ash. Other heavy metals such as Zn, Pb and Cd are volatile heavy metals, which react with chlorine in the fly ash under high temperature to undergo chlorination reaction and volatilize into the secondary fly ash, thereby obtaining secondary fly ash mainly composed of chlorides such as NaCl, KCl, PbCl2, ZnCl2 and CdCl2, wherein the grade of Pb and Zn reaches more than 4%, and can be used as raw materials for industrial Pb and Zn.
[0043] The tailings obtained by the present invention are geopolymer materials, which can stimulate their gelling activity under the stimulation of an alkaline activator and can be used as a raw material for cement. However, after recovering metallic iron through other similar high-temperature reduction processes such as the direct reduction process of iron tailings, the slag obtained is still solid waste and there is no suitable utilization method. The present invention makes full use of the carbon in the fly ash itself, does not use fossil fuels such as coke and coal, and saves energy. At the same time, compared with direct melting of fly ash, this process can reduce the reduction temperature to below 1300°C, reduce carbon emissions, and meet the strategic policy of carbon emission reduction.
[0044] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0045] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing ferroalloy and geopolymer materials using waste incineration fly ash and iron tailings, characterized in that: The following steps are involved: The waste incineration fly ash and the finely ground iron tailings are mixed and then co-reduction roasted at 1050-1200° C. to obtain a roasted product; During the roasting process, the flue gas is collected to obtain secondary fly ash; the roasted product is then cooled and ground and magnetically separated to obtain ferroalloy and geopolymer materials; The mass percentages of the main components of the iron tailings are as follows: Fe2O3 5-25%, SiO2 64.56-70%, Al2O3 5-25%, CaO 2-20%, MgO 2-10%; the iron in the iron tailings mainly exists in the form of magnetite and pyroxene; Geopolymer material is an amorphous inorganic material composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, and the content of glass in the geopolymer material is ≥90%; The geopolymer material is finely ground twice to obtain geopolymer material powder; the geopolymer material powder, alkali activator and water are evenly mixed to obtain a mixture, and the compressive strength of the mixture after 28 days is ≥80Mpa, and the flexural strength is ≥8Mpa.
2. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 1, characterized in that: The fine grinding method of the iron tailings is as follows: the iron tailings are finely ground by a ball mill or a rod mill, the grinding concentration is 55-70%, the grinding time is 5-25 minutes, and the fineness of the iron tailings after fine grinding reaches -150μm≥80%.
3. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 1, characterized in that: The co-reduction roasting method is as follows: after uniformly mixing the waste incineration fly ash and the finely ground iron tailings, the co-reduction roasting is performed at 1050-1200°C for 30-150 minutes to obtain a roasting product, which is mainly composed of ferroalloy and geopolymer materials.
4. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 3, characterized in that: The roasted product is naturally cooled or water quenched and then finely ground and magnetically separated. The fineness of the roasted product after fine grinding reaches -0.15mm with a mass fraction of 30-70%. The magnetic field strength of the magnetic separation is 0.6-1.5KGs. The magnetic product is ferroalloy and the non-magnetic product is geopolymer material.
5. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 1, characterized in that: The mass percentage of the waste incineration fly ash is 20-80%, and the mass percentage of the finely ground iron tailings is 20-80%.
6. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 5, characterized in that: The mass percentages of the main elements in the waste incineration fly ash are as follows: Ca 10-60%, C 5-20%, Si 0.1-10%, Al 0.1-8%, Cl 10-30%, Fe 0.1-8%, Na 0.1-6%, K 0.1-6%, S 0.1-3%. The waste incineration fly ash also includes the following mass percentages of heavy metal elements: Zn 0-1%, Pb 0-1%, Cr 0-1%, Cu 0-1%, Ni 0-1%, Cd 0-1%.
7. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to any one of claims 1 to 6, characterized in that: During the co-reduction roasting process, the flue gas is captured by a flue gas capture device to obtain secondary fly ash, which is a mixture of NaCl 10-80%, KCl 10-80%, PbCl2 1-10%, ZnCl2 1-10% and CdCl2 0-10%.
8. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 7, characterized in that: The geopolymer material is finely ground for the second time to a mass fraction of -45µm ≥ 70% and a specific surface area ≥ 400m 2 / kg, to obtain geopolymer material powder.
9. The method for preparing ferroalloy and geopolymer materials by using waste incineration fly ash and iron tailings according to claim 8, characterized in that: The alkali activator is mainly one or more of cement, Ca(OH)2, NaOH, lime and water glass, the amount of the geopolymer material is 80-96%, the amount of the alkali activator is 4-20%; the water-cement ratio is 0.4-0.7, wherein the mass of the ash is the sum of the geopolymer material and the alkali activator.
Citation Information
Patent Citations
Method for preparing alloy iron and glass ceramics
CN109020231A